Trends and Species Diversity of Non-tuberculous Mycobacteria Isolated From Respiratory Samples in Northern China, 2014–2021 - Sun, Qing; Yan, Jun; Liao, Xinlei; Wang, Chaohong; Wang, Chenqian; Jiang, Guanglu; Dong, Lingling; Wang, Fen; Huang, Hairong; Wang, Guirong; Pan, Junhua (Frontiers in Public Health, 2022)
Background Pulmonary non-tuberculous mycobacteria (NTM) infection has become a public health concern in China and around the world. The objective of this study was to describe the longitudinal changes in the frequency and diversity of NTM in northern China. Methods We retrospectively analyzed data on mycobacterium species in Beijing Chest Hospital from January 2014 to December 2021. The isolates were identified to species level by targeted DNA sequencing. Results After excluding duplicates, 1,755 NTM strains were analyzed, which were from 27 provinces in China over 8 years. Among all mycobacteria, the proportion of NTM increased each year, from 4.24% in 2014 to 12.68% in 2021. Overall, 39 different NTM species were identified, including 23 slow growing mycobacteria (SGM) and 16 rapid growing mycobacteria (RGM). The most common species were M. intracellulare (51.62%), M. abscessus (22.22%), M. kansasii (8.32%), M. avium (7.75%) and M. fortuitum (2.05%). The number of NTM species identified also increased each year from 9 in 2014 to 26 in 2021. Most species showed stable isolation rates over the years; however, the proportion of M. avium increased from 3.85 to 10.42% during the study period. Besides, 81 non-mycobacteria strains, including Gordonia (21 isolates), Nocardia (19 isolates) and Tsukamurella (17 isolates), etc., were also discovered. Conclusion The proportion of NTM and species diversity increased considerably in northern China from 2014 to 2021. M. intracellulare was the most common NTM isolated among respiratory specimens, followed by M. abscessus and M. kansasii. Rare NTM species and non-mycobacteria pathogens also need attention.